Comparative analysis of seed and seedling irradiation with gamma rays and carbon ions for mutation induction in Arabidopsis - Hase, Yoshihiro; Satoh, Katsuya; Kitamura, Satoshi (Frontiers in Plant Science, 2023)
The molecular nature of mutations induced by ionizing radiation and chemical mutagens in plants is becoming clearer owing to the availability of high-throughput DNA sequencing technology. However, few studies have compared the induced mutations between different radiation qualities and between different irradiated materials with the same analysis method. To compare mutation induction between dry-seeds and seedlings irradiated with carbon ions and gamma rays in Arabidopsis, in this study we detected the mutations induced by seedling irradiation with gamma rays and analyzed the data together with data previously obtained for the other irradiation treatments. Mutation frequency at the equivalent dose for survival reduction was higher with gamma rays than with carbon ions, and was higher with dry-seed irradiation than with seedling irradiation. Carbon ions induced a higher frequency of deletions (2−99 bp) than gamma rays in the case of dry-seed irradiation, but this difference was less evident in the case of seedling irradiation. This result supported the inference that dry-seed irradiation under a lower water content more clearly reflects the difference in radiation quality. However, the ratio of rearrangements (inversions, translocations, and deletions larger than 100 bp), which are considered to be derived from the rejoining of two distantly located DNA breaks, was significantly higher with carbon ions than gamma rays irrespective of the irradiated material. This finding suggested that high-linear energy transfer radiation induced closely located DNA damage, irrespective of the water content of the material, that could lead to the generation of rearrangements. Taken together, the results provide an overall picture of radiation-induced mutation in Arabidopsis and will be useful for selection of a suitable radiation treatment for mutagenesis.